Function and Distribution of the Wamide Neuropeptide Superfamily in Metazoans - Williams, Elizabeth A. (Frontiers in Endocrinology, 2020)
The Wamide neuropeptide superfamily is of interest due to its distinctive functions in regulating life cycle transitions, metamorphic hormone signalling, and several aspects of digestive system function, from gut muscle contraction to satiety and fat storage. Due to variation among researchers in naming conventions, a global view of Wamide signalling in animals in terms of conservation or diversification of function is currently lacking. Here, I summarize the phylogenetic distribution of Wamide neuropeptides based on current data and describe recent findings in the areas of Wamide receptors and biological functions. Common trends that emerge across Cnidarians and protostomes are the presence of multiple Wamide receptors within a single organism, and the fact that Wamide signalling likely functions across an extensive variety of biological systems, including visual, circadian and reproductive systems. Important areas of focus for future research will be in the further identification of Wamide-receptor pairs, confirmation of the phylogenetic distribution of Wamides through largescale sequencing and mass spectrometry, and assignment of different functions to specific subsets of Wamide-expressing neurons. More extensive study of Wamide signalling throughout larval development in a greater number of phyla is also important in order to understand the role of Wamides in hormonal regulation. Defining the evolution and function of neuropeptide signalling in animal nervous systems will benefit from an increased understanding of Wamide function and signalling mechanisms in a wider variety of organisms, beyond the original model systems.